2019
DOI: 10.1128/jvi.01177-18
|View full text |Cite
|
Sign up to set email alerts
|

Defining HIV-1 Envelope N-Glycan Microdomains through Site-Specific Heterogeneity Profiles

Abstract: The HIV-1 envelope (Env) glycans shield the surface of Env from the immune system and form integral interactions important for a functional Env. To understand how individual N-glycosylation sites (NGS) coordinate to form a dynamic shield and evade the immune system through mutations, we tracked 20 NGS in Env from HIV-transmitted/founder (T/F) and immune escape variants and their mutants involving the N262 glycan. NGS were profiled in a site-specific manner using a high-resolution mass spectrometry (MS)-based w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 46 publications
9
41
0
Order By: Relevance
“…To further clarify the function of the N262 glycans, we produced recombinant trimeric gp120 WEAU variants using our previously published approach that added a foldon and V5 and His tags to the gp120 (Hargett et al, 2019, Raska et al, 2014, Raska et al, 2008, Raska et al, 2010. We confirmed that gp120 WEAU glycoproteins were exclusively produced as trimers ( Fig 5A).…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…To further clarify the function of the N262 glycans, we produced recombinant trimeric gp120 WEAU variants using our previously published approach that added a foldon and V5 and His tags to the gp120 (Hargett et al, 2019, Raska et al, 2014, Raska et al, 2008, Raska et al, 2010. We confirmed that gp120 WEAU glycoproteins were exclusively produced as trimers ( Fig 5A).…”
Section: Resultsmentioning
confidence: 53%
“…The glycopeptides for each NGS were expressed as relative abundance of each individual N-glycopeptide at each site for each rgp120 variant ( Fig 6A). Three different types of heterogeneity were observed that categorized individual NGS as (i) predominantly high-mannose glycans, (ii) predominantly complex glycans, and (iii) a mixed population of both high-mannose and complex glycans ( Fig EV2B) (Hargett et al, 2019). N-glycan sitespecific heterogeneity profiles of the four WEAU rgp120 trimers are shown in Fig 6A (Behrens et al, 2017).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations